Domestic Regulation and Global Movement of Skilled Professionals : A Case Study of Indian Professionals in the United States - World Bank (Washington, DC, 2013)
Changes in demographics and patterns of investment in human capital are creating opportunities for international trade in professional services. As populations in rich countries age, developing countries are seeing an increase in the proportion of working-age people. At the same time, the richest countries are investing proportionally less than middle income countries in engineering and technical human capital. In India, the largest developing country exporter of skilled services, the supply of educated manpower has been rising rapidly. In the U.S., the largest single importer of skilled services demand for reasonably-priced, skilled workers like doctors, engineers, accountants and other high skilled professions is outpacing domestic supply. The movement of professionals across countries faces explicit barriers, such as restrictive visa regimes, and implicit impediments in the form of regulatory requirements to obtain qualifications, training and experience and licenses even when a service provider is already qualified and licensed in another jurisdiction. This paper focuses on the implicit impediments. Domestic regulations such as licensing and qualification requirements and procedures have a profound effect on services trade, but their analysis has proved elusive. Sifting the legitimate from the protectionist is far from straightforward. Nevertheless, we take a first step in this analysis, focusing on how regulatory requirements and procedures impact on Indian doctors, engineers, architects and accountants when they wish to practice their profession in the United States.